Performanţa României în domeniul dezvoltării umane - Mărginean, Ioan (Calitatea Vieții, 2022)
The article focuses on the analysis of Romania’s performance in the field of human development (HD), as it is presented in the Human Development Reports which the United Nations Development Program started in 1990. This performance is understood as a process of broadening the possibilities of people’s choices, and as the level of people’s welfare. It is about leading a healthy life, for as long as it is possible, about being educated and about having a decent standard of life (HDR, 1990). Each of the Human Development Reports issued so far was an event, whose information was much debated. The 2010 issue (20th anniversary) changed part of the indicators used for Human Development Index (HDI) calculation, the new indicators being expected to measure better country performance. More exactly, from the four indicators taken into calculation before 2010, which were set after several modifications: life expectancy, Gross Domestic Product (GDP), literacy rates and school enrolment rate, only the first one remained. The GDP was replaced by the Gross National Income (GNI), while in terms of education, the indexes calculate the mean years of schooling (MYS) of the people aged 25 and more, and the expected years of schooling (considering the actual yearly school enrolments). IHD calculation also changed: the geometric average of the indicators describing the three subcomponents (standardized in the interval 0–1) is used instead of the arithmetic mean of the indicators. The new formula was applied retroactively for several years, so that historic comparisons can be done. The surprise, to call it so, is that, using the new measurements, Romania stands somehow better, even if the historic trend didn’t change. Thus, while according to both the old and new calculations, IHD values decreased in Romania during the early years of transition, the decrease from the initial period has been recovered only in 2000–2005, while slight increases have been recorded in the last year of reporting. The better performance of Romania in HD is for MYS indicator and for EYS also. All these changes will be analysed together with several other information regarding the processes of inequality in human development.